Priming exercise accelerates oxygen uptake kinetics during high-intensity cycle exercise in middle-aged individuals with type 2 diabetes - Rocha, Joel; Gildea, Norita; O’Shea, Donal; Green, Simon; Egaña, Mikel (Frontiers in Physiology, 2022)
Background: The time constant of the primary phase pulmonary oxygen uptake kinetics (V̇O2 τp) during submaximal exercise is impaired (slowed) in middle-aged individuals with type 2 diabetes (T2D), partly due to limitations in oxygen supply to active muscles. We tested the hypothesis that a high-intensity “priming” exercise (PE) would speed V̇O2 τp during a subsequent high-intensity cycling exercise in T2D due to enhanced oxygen delivery. Methods: Eleven (4 women) middle-aged individuals with uncomplicated T2D and 11 (4 women) non-diabetic controls completed four bouts of constant-load high-intensity transitions, commencing from an ‘unloaded’ baseline of 10 W. Two bouts were completed without PE and two were preceded by PE. V̇O2 kinetics were calculated from continuously measured breath-by-breath data, and muscle deoxygenation (i.e., deoxygenated haemoglobin and myoglobin, [HHb+Mb]) kinetics were measured by near-infrared spectroscopy at the vastus lateralis muscle. Results: At baseline V̇O2 τp, was significantly slower (P < 0.001) in participants with T2D (48 ± 6 s) than controls (34 ± 2 s) but PE significantly reduced V̇O2 τp (P < 0.001) in T2D (32 ± 6 s) so that post-PE it was not different compared with controls (34 ± 3 s). The amplitude of the V̇O2 slow component (As) subsequent to PE was reduced (P < 0.001) in both groups (T2D: 0.26 ± 0.11 to 0.16 ± 0.07 l/min; Control: 0.33 ± 0.13 to 0.25 ± 0.14 l/min), while [HHb+Mb] kinetics remained unchanged. Conclusion: These results suggest that in middle-aged men and women with T2D, PE speeds V̇O2 τp likely by a better matching of O2 delivery to utilisation and reduces the V̇O2 As during a subsequent high-intensity exercise.